Dribbling determinants in sub-elite youth soccer players - Zago, M.; Piovan, A. G.; Annoni, I.; Ciprandi, D.; Iaia, F. M.; Sforza, C. (Journal of Sports Sciences, 2016)
Dribbling speed in soccer is considered critical to the outcome of the game and can assist in the talent identification process. However, little is known about the biomechanics of this skill. By means of a motion capture system, we aimed to quantitatively investigate the determinants of effective dribbling skill in a group of 10 Under-13 sub-elite players, divided by the median-split technique according to their dribbling test time (faster and slower groups). Foot-ball contacts cadence, centre of mass (CoM), ranges of motion (RoM), velocity and acceleration, as well as stride length, cadence and variability were computed. Hip and knee joint RoMs were also considered. Faster players, as compared to slower players, showed a 30% higher foot-ball cadence (3.0 ± 0.1 vs. 2.3 ± 0.2 contacts/s, P < 0.01); reduced CoM mediolateral (0.91 ± 0.05 vs. 1.14 ± 0.16 m, P < 0.05) and vertical (0.19 ± 0.01 vs. 0.25 ± 0.03 m, P < 0.05) RoMs; higher right stride cadence (+20%, P < 0.05) with lower variability (P < 0.05); reduced hip and knee flexion RoMs (P < 0.05). In conclusion, faster players are able to run with the ball through a shorter path in a more economical way. To effectively develop dribbling skill, coaches are encouraged to design specific practices where high stride frequency and narrow run trajectories are required.